Prevalence and morphological characterisation of Echinococcus granulosus from north India - Singh, Balbir Bagicha (Springer India, 2012)
The purpose of this study was to document the prevalence and to analyze morphological characteristics from hydatid cysts to test their suitability for strain identification. In the present study, 4,130 animals, including 278 cattle, 298 buffaloes, 760 sheep, 2,439 goat and 355 pigs were examined for the presence of hydatid cysts on post-mortem inspection at different slaughter houses/shops in northern India. Morphological characteristics from hydatid cysts were analyzed to test their suitability for strain identification. For statistical analysis, five variables were considered: number of hooks per rostellum, blade length of large and small hooks, and total length of large and small hooks. Principal component analysis was applied for analysis of morphological parameters. Out of a total of 4,130 animals examined, 66 were positive for hydatid cysts (prevalence 1.598 %). The prevalence of hydatid cysts was highest in cattle (5.39 %) followed by buffaloes (4.36 %), pigs (3.09 %), sheep (2.23 %) and goat (.41 %). The results indicate significant prevalence of hydatidosis in all the food producing animals and further that morphological analysis can also be used as a valid criterion for differentiation of different strains of E. granulosus particularly in developing countries where molecular studies could not be performed due to lack of infrastructure or financial constraints.